2022
DOI: 10.3389/fvets.2022.842259
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum and Cadmium Co-induce Mitochondrial Quality Control Disorder via FUNDC1-Mediated Mitophagy in Sheep Kidney

Abstract: Molybdenum (Mo), fundamental trace mineral for animals and plants, but undue Mo damages animal health. Cadmium (Cd) is a toxic heavy metal that exists in the environment. Nevertheless, the mechanism of Mo and Cd on mitochondrial quality control are still indistinct. The objective of this research was to explore the effects of mitophagy on mitochondrial quality control via the FUNDC1-mediated by Mo and Cd in sheep kidney. Forty-eight 2-month-old sheep were stochastically divided into four groups, as shown below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Increasing evidence has shown that Cd‐induced mitochondrial dysfunction is associated with the reduced expression and activity of SIRT1 40–42 . To determine whether SIRT1 is involved in Cd‐induced mitochondrial dysfunction in PC12 and cerebral cortical neurons, we examined MMP and intracellular ATP levels, which are markers of mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that Cd‐induced mitochondrial dysfunction is associated with the reduced expression and activity of SIRT1 40–42 . To determine whether SIRT1 is involved in Cd‐induced mitochondrial dysfunction in PC12 and cerebral cortical neurons, we examined MMP and intracellular ATP levels, which are markers of mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…It was speculated that Cd caused mitochondrial disfunction, decreased Sirt3, and increased oxidative stress, which led to activation of BNIP3dependent mitophagy as well as PINK1/Parkin-dependent mitophagy (Zhang et al, 2021b). It was observed that the level of another mitophagy receptor-FundC1-could also be elevated, together with a decrease in the Sirt3 mRNA level after Cd and Mo intoxication (Wu et al, 2022). However, a decline in Sirt3 could only be a consequence of the accumulation of damaged mitochondria and not cause mitophagy on its own.…”
Section: Sirtuin 3 and Mitophagymentioning
confidence: 99%
“…Environmental Mo and Cd levels are rapidly increasing due to industrial production and human activities. Numerous previous reports have suggested that Mo and Cd have adverse effects on animal and human health 11,12 . However, the underlying toxicological mechanisms of Cd and/or Mo in poultry have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous reports have suggested that Mo and Cd have adverse effects on animal and human health. 11,12 However, the underlying toxicological mechanisms of Cd and/or Mo in poultry have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%